2015
DOI: 10.3748/wjg.v21.i5.1488
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21/RASA1 axis affects malignancy of colon cancer cellsviaRAS pathways

Abstract: RASA1 is a target gene of miR-21, which promotes malignant behaviors of RKO cells through regulation of RASA1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 24 publications
1
44
2
Order By: Relevance
“…RASA1 in addition to its RasGAP activity has been speculated to be a RAS effector mediating the cellular effects of RAS through its interaction with p190RhoGAP and the subsequent inhibition of Rho activation (38). In agreement with the work reported here, in the colorectal cancer cell line RKO, decreased RASA1 expression mediated by miR-21 enhanced RAS signaling and invasion through transwells (42). …”
Section: Discussionsupporting
confidence: 91%
“…RASA1 in addition to its RasGAP activity has been speculated to be a RAS effector mediating the cellular effects of RAS through its interaction with p190RhoGAP and the subsequent inhibition of Rho activation (38). In agreement with the work reported here, in the colorectal cancer cell line RKO, decreased RASA1 expression mediated by miR-21 enhanced RAS signaling and invasion through transwells (42). …”
Section: Discussionsupporting
confidence: 91%
“…Increasing number of studies suggested that miRNAs affect the progression, pathogenesis classification, diagnosis, and prognosis of cancer 8, 9, 10, 11.Recently, increased miRNAs have been implicated in the digestive diseases 12, 13, 14.Several studies have found that miR‐21, miR‐17, miR‐31, miR‐15, and others were critically involved in the pathogenesis of colorectal cancer 15, 16, 17, 18. miR‐17‐92 cluster consisted of six miRNAs (miR‐17, miR‐18a, miR‐19a, miR‐20a, miR‐19b, miR‐92a) and two paralogs (miR‐106b and miR‐106a).…”
Section: Introductionmentioning
confidence: 99%
“…8 RASA1 contributed to miR-335Yinduced tumor cell invasion and migration in gastric cancer 9 and promoted miR-21Ymediated malignancy in colon cancer cells. 10 However, the exact role of RASA1 in the cervical cancer remains to be understood, so we next focused on how miR-21/RASA1 played a role in lymph node metastasis in cervical cancer.…”
mentioning
confidence: 99%